Flowering phenology of Mediterranean Quercus species in different locations (Córdoba, SW Iberian Peninsula) (Acta botánica malacitana, 2007)
Periodical qualitative and quantitative checking of flowering phases was carried out over six growing seasons (1997-2002) for the three Mediterranean Quercusspecies found in Sierra Morena (Córdoba, SW Spain): Q. ilex L. ssp. ballota (Desf.) Samp., Q. coccifera L. and Q. suber L. A total of 60 individuals were selected. Additionally, 30 Quercus ilex ssp. ballota individuals were selected and studied in Sierras Subbéticas (Priego de Córdoba, SW Spain) in 1999 and 2000. Morphological changes occurring at different points in each phenological phase were charted. Among species differences were found for inflorescences/male and female flowers, in terms of the phenological flowering sequence. Male inflorescences displayed a more homogeneous development. All individuals and populations were proterandrous. Phenological trends and ranges were charted. Although trends varied with species and year, the overall phenological trend seemed to fit a sigmoid curve in all cases, increasing with phenological development. Shorter ranges were obtained in years with warmer springs, and longer ranges in colder years. Moreover, phenological range differed as a function of species and location. In general, Q. ilex ssp. ballota flowered earlier than the rest, Q. suber displaying the latest flowering period. Individuals located at lower altitudes and facing the sun flowered earlier, followed in most years by those located at higher altitudes. Thus, Q. ilex ssp. ballota flowered earlier in Sierra Morena than in the higher-altitude Sierras Subbéticas.